Effect of Encapsulated Beet Extracts (Beta vulgaris) Added to Yogurt on the Physicochemical Characteristics and Antioxidant Activity - Martha A. Flores-Mancha; Martha G. Ruíz-Gutiérrez; Rogelio Sánchez-Vega; Eduardo Santellano-Estrada; América Chávez-Martínez (Molecules, 2021)
Beet has been used as an ingredient for functional foods due to its high antioxidant activity, thanks to the betalains it contains. The effects of the addition of beet extract (liquid and lyophilized) on the physicochemical characteristics, color, antioxidant activity (AA), total betalains (TB), total polyphenols (TP), and total protein concentration (TPC) were evaluated on stirred yogurt. The treatments (T1-yogurt natural, T2-yogurt added with beet juice, T3-added extract of beet encapsulated with maltodextrin, and T4-yogurt added with extract of beet encapsulated with inulin) exhibited results with significant differences (p < 0.05). The highest TB content was observed in T2 (209.49 ± 14.91), followed by T3 (18.65 ± 1.01) and later T4 (12.96 ± 0.55). The highest AA was observed on T2 after 14 days (ABTS˙ 0.819 mM TE/100 g and DPPH˙ 0.343 mM TE/100 g), and the lowest was found on T1 at day 14 (ABTS˙ 0.526 mM TE/100 g and DPPH˙ 0.094 mM TE/100 g). A high content of TP was observed (7.13 to 9.79 mg GAE/g). The TPC varied between 11.38 to 12.56 µg/mL. The addition of beet extract significantly increased AA in yogurt, betalains being the main compounds responsible for that bioactivity.